Morphology and properties of neutralized chitosan-cellulose nanocrystals biocomposite films. (20th January 2017) - Corsello, F.A.; Bolla, P.A.; Anbinder, P.S.; Serradell, M.A.; Amalvy, J.I.; Peruzzo, P.J.
Highlights: A good incorporation of the cellulose nanocrystals into chitosan matrix was obtained at concentrations below 5 wt%. Neutralization process affects the properties of chitosan-cellulose nanocrystals biocomposite films, with a high impact on the water resistance (improved) and antibacterial properties (worsened). Optimization of the neutralization process in the design of CH-based nanocomposite active films is necessary to obtain a balance between the properties. Abstract: Chitosan/cellulose nanocrystals (CH-CN) films were obtained by casting of dispersions, and treated with NaOH for neutralization proposes. The composition of films was varied from 1 to 10 wt.% of CN. Changes in the morphology of the systems were correlated with the different properties studied. FTIR revealed the presence of a weak interaction between the polymer matrix and nanofiller, confirmed by a slightly increase in thermal stability. SEM images suggested that incorporating CN amounts higher than 3 wt.% generates phase-segregated systems, and SAXS showed that CH avoid the typical organization of CN at concentrations below 5 wt.%. Improved performance against water was obtained in composite materials comparing to the pure polymer matrix, as well as CH and CH-CN films did not show antibacterial activity demonstrating that remnant acetic acid, when no neutralization step is done, plays an important role in this property.